DESAIN DAN IMPLEMENTASI REAL-TIME MULTIPOINT VIDEO TRANSMISSION BERBASIS WEB - Hendro F. J. Lami; Stephanie I. Pella (Universitas Nusa Cendana, 2012)
Education world of Indonesia experiences development along with integration between conventional study and e-learning bases method on web. Some universities in Indonesia offers service e-learning to base on web with a few content interaktif which can be exploited for expansion of quality of education. Content e-learning for example upload/download matter bases on document, chatting, live video streaming, and video conference. University of Nusa Cendana (Undana) also does system development of study of e-learning bases on web. Now content which on the market still limited to upload and download document. Video service conference have been implementation, but communications only support communications point-to-point and has not integrated with website elearning. Based on the limitation hence writer wish to develop the system becomes communications multipoint to base on web and can be integrated with website e-learning undana.